2011
DOI: 10.1093/gbe/evr095
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Different Inverted Repeat Copies from the Chloroplast Genomes of Pinaceae and Cupressophytes and Influence of Heterotachy on the Evaluation of Gymnosperm Phylogeny

Abstract: The relationships among the extant five gymnosperm groups—gnetophytes, Pinaceae, non-Pinaceae conifers (cupressophytes), Ginkgo, and cycads—remain equivocal. To clarify this issue, we sequenced the chloroplast genomes (cpDNAs) from two cupressophytes, Cephalotaxus wilsoniana and Taiwania cryptomerioides, and 53 common chloroplast protein-coding genes from another three cupressophytes, Agathis dammara, Nageia nagi, and Sciadopitys verticillata, and a non-Cycadaceae cycad, Bowenia serrulata. Comparative analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
181
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(193 citation statements)
references
References 68 publications
12
181
0
Order By: Relevance
“…A complete representation can be found in Supplemental Figure S1. IR A regions were lost in Cupressophytes [21,22]. The two-step model in the Pinaceae could also apply to the 424 bp of IR left in C. deodara.…”
Section: Dynamic Divergence Of Ir Copiesmentioning
confidence: 96%
See 3 more Smart Citations
“…A complete representation can be found in Supplemental Figure S1. IR A regions were lost in Cupressophytes [21,22]. The two-step model in the Pinaceae could also apply to the 424 bp of IR left in C. deodara.…”
Section: Dynamic Divergence Of Ir Copiesmentioning
confidence: 96%
“…2B, C) [6]. It also has been shown that different IR copies were lost in the cpDNAs of the Pinaceae and Cupressophytes of gymnosperms [21]. IR B regions were lost in Pinaceae in a two-step model, and only 495 bp were left in P. thunbergii, whereas 1.…”
Section: Dynamic Divergence Of Ir Copiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Homoplastic mutations occurring along the long external branches can obscure the true phylogenetic signal on the internal branches, then long-branch attraction (LBA) occurs, with the long branches erroneously clustered together45. The LBA artifact was suggested to adversely affect the accuracy of tree reconstruction in many phylogenetic studies67891011. It could be amplified in phylogenomics, thereby resulting in a strongly supported but incorrect phylogeny612.…”
mentioning
confidence: 99%